A photocatalyst for efficiently degrading organic pollutants and its preparation method

By modifying the combination of carbon nanotubes and nanozirconia, a high-efficiency photocatalyst is formed, which solves the problem of low efficiency in degradation of organic pollutants in the prior art, and realizes effective degradation of organic pollutants and improves the reaction activity of photocatalysts. efficiency.

CN118437353BActive Publication Date: 2024-12-17JIANGXI YISHENG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410552101.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2024-12-17
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

The prior art is inefficient in degrading organic pollutants, and cannot completely remove pollutants in wastewater, resulting in concentrated or degradation of pollutants to another stage, increasing treatment costs and environmental risks.

Method used

通过改性碳纳米管放电等离子烧结制得多壁结构,并在其表面静电吸附纳米氧化锆等光催化剂,形成高效的光催化剂,利用光生电子及空穴共同作用氧化有机污染物,增强反应活性 loci and efficiency.

Benefits of technology

It improves the reaction activity and efficiency of the photocatalyst, can effectively degrade organic pollutants into small molecule products, reduces the chance of electron hole recombination, and improves the photocatalytic effect and degradation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a novel photocatalyst for efficiently degrading organic pollutants and a preparation method thereof, and relates to the technical field of photocatalysts. The present invention utilizes vacuum high-temperature heat treatment of carbon nanotubes to form a multi-wall structure, thereby promoting electron transfer, increasing the active sites and reaction intensity of the photocatalytic reaction, and then, by electrostatically adsorbing nano-photocatalytic particles mainly composed of nano-zirconium oxide on the surface of the carbon nanotubes, oxidizing and decomposing organic pollutants into small molecular products under the combined effect of photogenerated electrons and holes, thereby achieving photocatalytic action, and the multi-wall structure of the carbon nanotubes enables the zirconium oxide particles to maintain a cubic crystal form for a long time, thereby enhancing the photocatalytic effect, and at the same time, the larger specific area of ​​the nanoparticles increases the active sites of the substrate in contact with the reaction substrate, further improving the photocatalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to a photocatalyst for efficiently degrading organic pollutants and a preparation method thereof. Background Art

[0002] Photocatalytic technology is a green technology with important application prospects in the fields of energy and environment. In recent years, the research and development of photocatalytic application technology has been very rapid. This new technology has the advantages of low energy consumption, simple operation process, mild reaction conditions, etc. It can completely oxidize organic matter in water, air and soil into non-toxic and harmless substances at room temperature, avoiding secondary pollution. In particular, it has outstanding performance in degrading organic pollutants, and can effectively degrade a variety of organic wastewaters including antibiotic pharmaceutical wastewater, sulfur-containing fuel wastewater, fermentation production wastewater, fine chemical wastewater, etc., to meet emission standards.

[0003] Due to the development of economy and society and the progress of science and technology, the natural environment has also been greatly damaged, and the problem of water pollution has become increasingly serious. In addition to inorganic pollutants, water bodies also contain a large amount of organic pollutants, which affect the ecosystem in the form of toxicity and reduction of dissolved oxygen in water, and endanger human health; because pollutants in wastewater must be effectively removed to make the water clean and reusable, wastewater treatment usually requires a high cost. However, existing conventional treatment methods cannot completely remove pollutants; instead, pollutants are concentrated or degraded to another stage. Among all other technologies, photocatalysis is considered to be one of the most effective wastewater treatment technologies, and is a powerful tool for converting solar energy into chemical energy. Summary of the invention

[0004] The purpose of the present invention is to provide a photocatalyst for efficiently degrading organic pollutants and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a photocatalyst for efficiently degrading organic pollutants, wherein the photocatalyst for efficiently degrading organic pollutants is prepared by loading the photocatalyst on modified carbon nanotubes through electrostatic adsorption.

[0006] Furthermore, the modified carbon nanotubes are prepared by spark plasma sintering of carbon nanotubes.

[0007] Furthermore, the photocatalyst is prepared by mixing nano zirconium oxide and other nanoparticles.

[0008] Furthermore, a method for preparing a photocatalyst for efficiently degrading organic pollutants comprises the following preparation steps:

[0009] (1) subjecting carbon nanotubes to spark plasma sintering to obtain modified carbon nanotubes;

[0010] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, ultrasonicate for 30-60 min, and stir at 200-400 rpm for 12-18 h to obtain intermediate A;

[0011] (3) Mix polyacrylamide and methanol, add photocatalyst, ultrasonicate for 30-60 min, stir at 200-400 rpm for 12-18 h, then dropwise add intermediate A, stir at 200-400 rpm for 2-6 h, and let stand for 10-20 h to obtain a photocatalyst that efficiently degrades organic pollutants.

[0012] Furthermore, the process parameters of the spark plasma sintering in step (1) are: vacuum degree of 6 Pa, heating rate of 100 K / min, temperature of 1400-2000° C., and holding time of 5-15 min.

[0013] Furthermore, in step (2), the mass ratio of polyethyleneimine, methanol and modified carbon nanotubes is 1-3:4-8:1.

[0014] Furthermore, in step (3), the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A is 1-3:4-8:1:6-12.

[0015] Furthermore, the photocatalyst in step (3) is prepared by mixing nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide in a mass ratio of 7:1:1:1.

[0016] Furthermore, the ultrasonic frequency in step (2) and step (3) is 21 kHz.

[0017] Furthermore, the dripping rate in step (3) is 0.5-3 mL / s.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention utilizes pretreatment of carbon nanotubes, and through vacuum high-temperature heat treatment, free carbon particles in the carbon nanotubes are vaporized, and at the same time, dangling bonds at defects in the tube wall are re-bonded with other carbon atom dangling bonds or ionic carbon atoms, thereby forming a multi-wall structure, promoting electron transfer, and increasing the active sites and reaction intensity of the photocatalyst reaction. Then, nano-photocatalytic particles mainly composed of nano-zirconium oxide are loaded on the surface of the carbon nanotubes through electrostatic adsorption. Under the combined effect of photogenerated electrons and holes, organic pollutants are oxidized and decomposed into small molecular products to achieve photocatalytic action. In the carbon nanotubes with a multi-wall structure, the zirconium oxide particles can maintain a cubic crystal shape for a long time, thereby reducing the chance of electron hole recombination and enhancing the photocatalytic effect. At the same time, the larger specific area of ​​the nanoparticles increases the active sites of the substrate in contact with the reaction substrate, further improving the photocatalytic efficiency. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the photocatalysts for efficiently degrading organic pollutants prepared in the following examples are as follows:

[0022] 50 mg of each photocatalyst prepared in the embodiment of the present invention and the comparative example were added to 100 mL of a tetracycline solution with a concentration of 20 mg / L, and ultrasonically homogenized. The mixture was reacted for 60 min in the absence of light to reach adsorption and desorption equilibrium. The mixture was then illuminated for 150 min under visible light with a wavelength of λ>420 nm to carry out photocatalytic degradation reaction. 3 mL of the sample was taken every 30 min, and the characteristic peak value of tetracycline in the solution was measured using a UV-visible spectrophotometer, converted into concentration, and the degradation rate was calculated.

[0023] Example 1

[0024] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1400°C, and holding time of 5 min, to obtain modified carbon nanotubes;

[0025] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21 kHz for 30 min, and stir at 200 rpm for 12 h to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 1:4:1;

[0026] (3) Nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21 kHz for 30 min, stirring was performed at 200 rpm for 12 h, then intermediate A was added dropwise at 0.5 mL / s, stirring was performed at 200 rpm for 2 h, and the mixture was allowed to stand for 10 h to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of the polyacrylamide, methanol, photocatalyst and intermediate A was 1:4:1:6.

[0027] Example 2

[0028] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0029] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 45 minutes, and stir at 300rpm for 15 hours to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 2:6:1;

[0030] (3) Nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, intermediate A was added dropwise at 1mL / s, and the mixture was stirred at 300rpm for 4 hours. The mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0031] Example 3

[0032] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 2000°C, and holding time of 15 min, to obtain modified carbon nanotubes;

[0033] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 60 minutes, and stir at 400rpm for 18 hours to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 3:8:1;

[0034] (3) Nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 60 minutes, and stirring was performed at 400rpm for 18 hours. Subsequently, intermediate A was added dropwise at 3mL / s, and stirring was performed at 400rpm for 6 hours. The mixture was allowed to stand for 20 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 3:8:1:12.

[0035] Comparative Example 1

[0036] (1) Mix polyethyleneimine and methanol, add carbon nanotubes, perform ultrasound at 21kHz for 30-60min, and stir at 300rpm for 15h to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and carbon nanotubes is 2:6:1;

[0037] (2) Nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, intermediate A was added dropwise at 1mL / s, and the mixture was stirred at 300rpm for 4 hours. The mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0038] Comparative Example 2

[0039] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0040] (2) Nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, modified carbon nanotubes were added, the mixture was stirred at 300rpm for 4 hours, and the mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of the polyacrylamide, methanol, photocatalyst and modified carbon nanotubes was 2:4:1:9.

[0041] Comparative Example 3

[0042] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0043] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 45 minutes, and stir at 300rpm for 15 hours to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 2:6:1;

[0044] (3) Nano-titanium oxide, nano-cadmium sulfide and nano-zinc oxide were mixed in a mass ratio of 1:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, intermediate A was added dropwise at 1mL / s, and the mixture was stirred at 300rpm for 4 hours. The mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0045] Comparative Example 4

[0046] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0047] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 45 minutes, and stir at 300rpm for 15 hours to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 2:6:1;

[0048] (3) Nano zirconium oxide, nano cadmium sulfide and nano zinc oxide were mixed in a mass ratio of 7:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, intermediate A was added dropwise at 1mL / s, and the mixture was stirred at 300rpm for 4 hours. The mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0049] Comparative Example 5

[0050] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0051] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 30-60min, and stir at 300rpm for 15h to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 2:6:1;

[0052] (3) Nano zirconium oxide, nano titanium oxide and nano zinc oxide were mixed in a mass ratio of 7:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, stirring was performed at 300rpm for 15 hours, and then intermediate A was added dropwise at 1mL / s, stirring was performed at 300rpm for 4 hours, and the mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0053] Comparative Example 6

[0054] (1) Placing the carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1700°C, and holding time of 10 min, to obtain modified carbon nanotubes;

[0055] (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, perform ultrasound at 21kHz for 45 minutes, and stir at 300rpm for 15 hours to obtain intermediate A; the mass ratio of polyethyleneimine, methanol, and modified carbon nanotubes is 2:6:1;

[0056] (3) Nano zirconium oxide, nano titanium oxide and nano cadmium sulfide were mixed in a mass ratio of 7:1:1 to obtain a photocatalyst; polyacrylamide and methanol were mixed, the photocatalyst was added, ultrasound was applied at 21kHz for 45 minutes, and the mixture was stirred at 300rpm for 15 hours. Subsequently, intermediate A was added dropwise at 1mL / s, and the mixture was stirred at 300rpm for 4 hours. The mixture was allowed to stand for 15 hours to obtain a photocatalyst for efficiently degrading organic pollutants; the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A was 2:4:1:9.

[0057] Effect example

[0058] Table 1 below shows the performance analysis results of the photocatalysts for efficiently degrading organic pollutants using Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0059] Table 1

[0060]

[0061] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention utilizes pretreatment of carbon nanotubes, and through vacuum high-temperature heat treatment, the free carbon particles in the carbon nanotubes are vaporized, and at the same time, the dangling bonds at the defects of the tube wall are re-bonded with other carbon atom dangling bonds or ionic carbon atoms, thereby forming a multi-walled structure, promoting electron transfer, and increasing the active sites and reaction intensity of the photocatalyst reaction. Then, nano-photocatalytic particles mainly composed of nano-zirconium oxide are loaded on the surface of the carbon nanotubes through electrostatic adsorption. Under the combined effect of photogenerated electrons and holes, organic pollutants are oxidized and decomposed into small molecular products to achieve photocatalytic action. In the multi-walled carbon nanotubes, the zirconium oxide particles can maintain a cubic crystal shape for a long time, thereby reducing the chance of electron-hole recombination and enhancing the photocatalytic effect. At the same time, the larger specific area of ​​the nanoparticles increases the active sites of the substrate in contact with the reaction substrate, further improving the photocatalytic efficiency.

[0062] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A photocatalyst for efficiently degrading organic pollutants, characterized in that: The method comprises the following preparation steps: (1) Placing carbon nanotubes in a vacuum environment of 6 Pa and performing spark plasma sintering with the following process parameters: heating rate of 100 K / min, temperature of 1400-2000°C, and holding time of 5-15 min, to obtain modified carbon nanotubes; (2) Mix polyethyleneimine and methanol, add modified carbon nanotubes, ultrasonicate for 30-60 min, and stir at 200-400 rpm for 12-18 h to obtain intermediate A; (3) Mix nano zirconium oxide, nano titanium oxide, nano cadmium sulfide and nano zinc oxide in a mass ratio of 7:1:1:1 to obtain a photocatalyst; mix polyacrylamide and methanol, add the photocatalyst, ultrasonicate for 30-60 min, stir at 200-400 rpm for 12-18 h, then dropwise add intermediate A, stir at 200-400 rpm for 2-6 h, and let stand for 10-20 h to obtain a photocatalyst for efficiently degrading organic pollutants.

2. The photocatalyst for efficiently degrading organic pollutants according to claim 1, characterized in that: In step (2), the mass ratio of polyethyleneimine, methanol and modified carbon nanotubes is 1-3:4-8:

1.

3. The photocatalyst for efficiently degrading organic pollutants according to claim 1, characterized in that: In step (3), the mass ratio of polyacrylamide, methanol, photocatalyst and intermediate A is 1-3:4-8:1:6-12.

4. The photocatalyst for efficiently degrading organic pollutants according to claim 1, characterized in that: The ultrasonic frequency in step (2) and step (3) is 21 kHz.

5. The photocatalyst for efficiently degrading organic pollutants according to claim 1, characterized in that: The dripping rate in step (3) is 0.5-3 mL / s.